2000
DOI: 10.1002/(sici)1097-0320(20000215)42:1<27::aid-cyto5>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric DNA ploidy, p53, PCNA, and c-erbB-2 protein expressions as predictors of survival in surgically resected gastric cancer patients

Abstract: In order to determine retrospectively the impact of some cytometric and immunohistochemical parameters on the overall survival of gastric cancer patients treated with surgery alone, paraffin‐embedded tumor samples from 137 gastric carcinoma patients undergoing curative resection from 1987–1993 were analyzed by flow cytometry (FCM) and immunohistochemistry (p53, c‐erbB‐2, and PCNA expression). FCM‐derived parameters were DNA ploidy and fraction of S‐phase cells (SPF). Multiple regression analysis was applied to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 41 publications
1
15
1
1
Order By: Relevance
“…The samples with nuclear p53 only (and negative for nuclear b-catenin) also showed higher ABI of 60% (Figure 4g; Po0.001) than those negative for both. These results are consistent with the report (Danesi et al, 2000) showing association between p53 overexpression and aneuploidy, and suggest the validity of our ABI analysis. They also indicate that b-catenin/TCF transcriptional activation contributes to CIN in the intestinal-type gastric cancer too, independent of the p53 status.…”
Section: Es Cells With High Abi Produce New Chromosomal Aberrationssupporting
confidence: 93%
See 1 more Smart Citation
“…The samples with nuclear p53 only (and negative for nuclear b-catenin) also showed higher ABI of 60% (Figure 4g; Po0.001) than those negative for both. These results are consistent with the report (Danesi et al, 2000) showing association between p53 overexpression and aneuploidy, and suggest the validity of our ABI analysis. They also indicate that b-catenin/TCF transcriptional activation contributes to CIN in the intestinal-type gastric cancer too, independent of the p53 status.…”
Section: Es Cells With High Abi Produce New Chromosomal Aberrationssupporting
confidence: 93%
“…In the intestinal-type gastric cancer, samples with nuclear b-catenin localization had higher ABI, with a stronger statistical significance (Figure 4e; P ¼ 0.014), whereas in the diffuse type, there was less correlation (Figure 4f; P ¼ 0.14). As nuclear expression of p53 is implicated in CIN in gastric cancer (Danesi et al, 2000), we also examined p53 (Figure 4d), and its relationship with ABI. For the intestinal-type gastric cancer, the samples negative for nuclear expression of both b-catenin and p53 showed ABI of 33% (Figure 4g).…”
Section: Es Cells With High Abi Produce New Chromosomal Aberrationsmentioning
confidence: 99%
“…When all patients were pooled they did not observe any clinical relevance [12]. In addition, Danesi et al suggested that DNA ploidy may act as a prognostic factor only in early-stage tumours (stages I and II) [13].…”
Section: Aneuploidy and Gastric Cancermentioning
confidence: 99%
“…Bu araş tır ma la rın ter si ne hiç bir kli ni ko pa to lo jik pa ra met re ile p53 ara sın da iliş ki sap ta ma yan ça-lış ma lar da var dır. [31][32][33][34] Sağ ka lım açı sın dan ya pı lan ça lış ma lar da Le e ve ark. 34 sa de ce dif füz tip kar sinom da, Ro vi el lo ve ark.…”
Section: Re Si̇munclassified